An evolutionary analysis of revenue management research in hospitality and tourism: Is there a paradigm shift?. Issue 2 (17th January 2020) - Denizci Guillet, Basak
Abstract : Purpose: The purpose of this study is to examine the evolution of revenue management (RM) research's intellectual structure in hospitality and tourism in an effort to initiate a creative discourse for RM scholars. Design/methodology/approach: Co-citation analysis was used to examine the reference list of 343 articles over a 35-year period (1983-2018). Co-citation analysis focused on subject clustering and source knowledge evolution. Five periods were created to investigate the evolution of the RM field in the hospitality and tourism industry. The paradigm shift approach was adopted to acquire a better understanding of scientific evolution. Findings: Findings indicated that from a Kuhnian perspective, RM research in hospitality and tourism did not go beyond the normal science phase. There is no current indication of anomalies in the form of conflict or questioning of the existing paradigms in RM research in hospitality and tourism. This might change, as the research in this realm develops further and evolves. Research limitations/implications: This study identified issues related to research themes that have the potential of moving RM research in hospitality and tourism to the next level, enabling the paradigm shift in this discipline. Originality/value: This study is instrumental in its outlook on the evolution of RM research's intellectual structure in hospitality and tourism. In addition, it is the first study that considers the concept of paradigm shift in RM research context in hospitality and tourism.